A linguagem dos direitos. O simbólico nas reclamações dos moradores de favelas - Marcus Cardoso (Ciências Sociais Unisinos)
Malinowski (2003), Gluckman (2006), Bohannan (1989), Geertz (2002) and Nader (1997) demonstrated that the laws reflect a particular conception of the world. Added to thisthat, even within a society the law is subject to multiple meanings. The code can be unique, but the way he's lived and thought vary (or vary) according to the social group together. To understand the demands for rights and the conflicts that arise from the perception that they are being disrespected, you must be aware of the significant universe of those involved in the situation. In this article, I discuss the correlation between conceptions of rights, dissatisfaction with the police and demands for respect, as presented by the inhabitants of Cantagalo and Pavao Pavãozinho. This approach allows us to ponder the possibilities and challenges of projects inspired by the philosophy of community policing created to operate in favelas and peripheries, since it takes into account what are the complaints and demands of the population "target" of these initiatives.